Visualization enhancement of bioinformatics software for genetic recombination via UCSC genome browser - Wong, Ryan Wei Jiat (2014)
The objective of the project is to enhance the visualization aspect of the Bioinformatics software, LDsplit. Its ability to estimate recombination hotspot-SNP associations is remarkable for future research. However the results, recombination profiles, cannot be visualized and utilized as well as many would like to.